Protected areas as a chance for the local development. The National Park of "Aigüestortes i Estany de Sant Maurici" as a dynamising element in its area of influence. - Farré Perdiguer Mariona; Enciso Rodriguez Joan Pere (European Regional Science Association (ERSA), 2003)
Recent times, many countries influenced by its citizens had followed a strategy of create natural or national parks. The overriding motive appears to be the preservation of a recognisable unique area of natural wealth. Nevertheless, recent years have seen a rising demand for wildlife viewing. In this sense, the demand of outdoor recreation in general and wildlife viewing in particular has grown rapidly. The problem is that too many visitors imply that the wilderness aspect of the recreational experience is watered down and second it affects the wildlife itself. The set of problems facing protected areas management has to do with the possibility of harmonising aims; preservation and recreational use. Generally, protected areas are settled on economically slum areas with high ageing rate, with important process of rural depopulation and under-staffed in terms of equipment, services and infrastructures. In this respect, a proper management of these natural areas could imply an economic and social revitalisation of such regions. This paper analyses the social and economic impact of the National Park of Aigüestortes i Estany de Sant Maurici on its influence zone. The Park is located in Catalonia in the heart of the Pyrenees and it's the most genuine representation of mountainous area. This paper analyses also the different alternatives that had been developed and considers others that could be introduced in order to achieve a greater complicity between local communities, visitors and managers by the reinforcement of the national park as a positive element for every one.
Keywords: 330